2022
DOI: 10.3389/fimmu.2022.835986
|View full text |Cite
|
Sign up to set email alerts
|

CCR2+ Macrophages Promote Orthodontic Tooth Movement and Alveolar Bone Remodeling

Abstract: During mechanical force-induced alveolar bone remodeling, macrophage-mediated local inflammation plays a critical role. Yet, the detailed heterogeneity of macrophages is still unknown. Single-cell RNA sequencing was used to study the transcriptome heterogeneity of macrophages during alveolar bone remodeling. We identified macrophage subclusters with specific gene expression profiles and functions. CellChat and trajectory analysis revealed a central role of the Ccr2 cluster during development, with the CCL sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Thus, we assume that the synchronous up-regulation of M1 and M2 could be the result of this macrophage heterogeneity in the late stage of the immune response induced by compression. This hypothesis is supported indirectly by single-cell sequencing results [ 31 ]. Furthermore, iNOS was the first marker to respond to mechanical stimulation, and did so earlier than Arg1 and IL-10.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, we assume that the synchronous up-regulation of M1 and M2 could be the result of this macrophage heterogeneity in the late stage of the immune response induced by compression. This hypothesis is supported indirectly by single-cell sequencing results [ 31 ]. Furthermore, iNOS was the first marker to respond to mechanical stimulation, and did so earlier than Arg1 and IL-10.…”
Section: Discussionmentioning
confidence: 82%
“…Also, trajectory analysis of single-cell RNA sequencing data further demonstrated that the proliferative differentiation of macrophages originated from the MHC-II clusters and expressed more genes for antigen processing and presentation [ 57 ]. In the present work, we recognized the MS4A6A gene as the final potential biomarker of the disease development after rigorous filtration and validation by external datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in the present study, the O + B group showed significant increases in four parameters, i.e., the trabecular bone volume, bone marrow volume, bone volume fraction, and trabecular thickness, indicating more bone formation in this group during OTM with BG material augmentation. This might have been caused by the recruitment of osteoclasts and inflammatory cells early in the remodeling process under mechanical force, leading to enhanced osteoclast-mediated bone resorption followed by osteoblast-mediated bone formation [6,28,29]. The process might accelerate the remodeling of the alveolar bone with bovine bone mineral grafts under mechanical force, resulting in more newly-formed bone tissues in the O + B group.…”
Section: Discussionmentioning
confidence: 99%